Object-oriented approach in developing knowledge base for a multimedia e-learning system - Mohd. Fairuz Mohd. Yusof; Rafisha Ramly; Ng, Kai-Li; Yeoh, Eng-Thiam; Robin Salim; Elandy, Kasturi Muthu (World Scientific and Engineering Academy and Society (WSEAS), 2005)
This paper describes the work of the research done to model a knowledge base. The knowledge base is one of the components of the Multimedia Knowledge Base E-Learning (MKBE-Leaming) project which is still in progress [1]. The paper discusses the modeling of the knowledge base architecture using Object-Oriented Analysis and Design (OOAD) [2]. The process of the modeling follows the Rational Unified Process (RUP) [3]. The model is visualized and documented using the Unified Modeling Language (UML) [2]. The outcome of the OOAD modeling is blueprints of the knowledge base architecture. The blueprints are made up of static and dynamic elements of the Analysis and Design Model. The whole idea of the architecture is to design new representation of knowledge base that includes teaching and learning objects.